Perbandingan Konsumtif Ibu Rumah Tangga Terhadap Minat Berbelanja antara Pasar Tradisional dan Modern Selama Pandemi - Maulana, Sahrul; Dawam, Aulia; Septiana, Aldila (Jurnal Pendidikan Ekonomi Undiksha, 2022)
The market as it is known is the location for buying and selling transactions, whether it be in the form of daily basic needs, clothing, and other goods. Markets that are well known to the wider community are the Traditional Market and the Modern Market. Housewives can be classified as one of the consumers, tend to have large consumptive behavior and are included in the consumer group who pays attention to various aspects of shopping, especially for shopping. The purpose of this study is that researchers have a goal to find out whether there are significant differences in the consumptive behavior of housewives towards shopping interest in traditional markets and modern markets during the COVID-19 pandemic in Klampis Timur Village. The variable of consumptive behavior has more influence on the variable of shopping interest in the modern market compared to the traditional market.